Application of Soy Protein Isolate Edible Coating for Mangosteen (Garcinia Mangostana) Storage - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Recently, the mangosteen has been noted to be an abundant source of a class of polyphenols known as xanthones It has a variety of health promoting properties including anti-inflammatory, anti-oxidant, and anti-cancer activity. Mangosteen fruits have a storage and marketable postharvest life of not more than one week under tropical conditions. In order to have supply of this fruit between harvest seasons, which ranges from two to four months depending on local production, it is necessary to use postharvest techniques for the extension of mangosteen shelf life. Application of soy protein isolate as edible coating could be considered as a useful approach to maintain its product quality during preservation. Ojective of the present study focused on the effect of soy protein isolate coating on some physicochemical, microbial and sensory characteristics of mangosteen during preservation. Optimal results showed that weight loss, pH, total soluble solids, titratable acidity and ascorbic acid; total plate count; sensory characteristics could be maintained at appropriate levels by coating mangosteen with 1.5% soy protein isolate.Keywords: Mangosteen, Soy protein isolate, Coating, Preservation, Physicochemical, Microbial, Sensory.